NP-001 Impact of an oral nutrition protocol in patients treated with elective radical cystectomy: a long term follow-up. (24th March 2020) - Declercq, P; Van der Aa, F; De Pourcq, L; Spriet, I
Abstract : Background and importance: Before we implemented an oral nutrition protocol, parenteral nutrition (PN) was standard of care after elective radical cystectomy (RC) patients in our hospital. PN is expensive, with often metabolic and infectious complications. Aim and objectives: The main objective of this study was to explore the impact of the introduction of an oral nutrition protocol on catheter-related bloodstream infection (CRBSI) incidence. Besides, length of stay and parenteral nutrition (PN) associated costs were compared. Materials and methods: In this large retrospective case-control study, before (PN group) and after the implementation of the oral nutrition protocol (since March 2010), two cohorts of 549 patients who underwent an elective RC were included. A central venous catheter was present in every patient, which is standard of care. The incidence of a CRBSI, the length of stay and PN associated costs were compared. Results: In both the control (June 2000–March 2010) and the case (March 2010–December 2017) group, an equal number of 549 patients were included. CRBSI was reduced from 22 (4%) to 10 (1.8%) (p=0.031). The median length of stay between both groups, 20 [17 – 25] days before vs. 17 [14 – 21] days after the implementation of the oral nutrition protocol, also differed significantly (p<0.001). Implementing the oral nutrition protocol resulted in a parenteral nutrition associated cost saving of €470 per patient. Conclusion and relevance: This large follow-up study showed that an oral nutrition protocol is associated with a reduction in CRBSI. Besides, postponing PN in favour of oral nutrition enhances recovery and is associated with cost savings. In conclusion, we believe that the clinically relevant results of our study are confirming that oral nutrition should be standard of care in elective regular RC patients.